A study to assess the impact of structured teaching programme on knowledge regarding tracheostomy care among staff nurses working in selected hospital of Kashmir - Bilques Qadir, Mir (International Journal of Nursing Research, 2023)
Tracheostomy care and tracheal suctioning are high-risk procedures. Tracheostomy patients aren’t seen only in intensive care units. As patients with more complex conditions are admitted to hospitals, an increasing number are being housed on general nursing units. Tracheostomy patients are at high risk for airway obstruction, impaired ventilation, and infection as well as other lethal complications. Skilled bedside nursing care can prevent these complications. Aim: The present study was aimed to enhance the knowledge of staff nurses regarding tracheostomy care & in turn reduce the risk of complications associated with the procedure. Materials and methods: A quantitative (pre-experimental) research study was conducted with “one group pre-test post-test research design to assess the level of knowledge regarding tracheostomy care among the staff nurses. The sample comprised of 60 staff nurses working in selected areas of the hospital. Stratified simple random sampling technique was used for the study. The tool utilized for the data collection was structured knowledge questionnaire. Results: The obtained data were analyzed by using the descriptive and inferential statistics. The mean post-test knowledge score (39.47) was significantly higher than the mean pre-test knowledge score (24.10) with the mean difference (15.37). There was a significant difference between pre-test and post-test knowledge score at p<0.05. The results of the study revealed that the planned teaching program was significantly effective in improving the knowledge of staff nurses. Conclusion: Hence, the study concluded that Staff nurses were having inadequate knowledge and structured teaching programme was effective in enhancing their knowledge regarding tracheostomy care.